2014
DOI: 10.1177/0004563214529937
|View full text |Cite
|
Sign up to set email alerts
|

The comparability of oxalate excretion and oxalate:creatinine ratio in the investigation of primary hyperoxaluria: review of data from a referral centre

Abstract: Oxalate:creatinine ratio and oxalate excretion were discordant in many patients, which is likely to be a result of intra-individual variation in creatinine output and imprecision in the collection itself. Some PH patients had urine oxalate within the reference range on occasion, and therefore it is not possible to exclude PH on the finding of a single normal result. A significant number of individuals had urine oxalate results well above the reference range who potentially have undiagnosed PH and are consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…Normal values considered as 100–460 μmol/day/1.73 m 2 of oxalate excretion. (Adequate collection was estimated via measuring 24 h creatinine of 0.1–0.2 mmol/kg/day) [9]. In cases of persistent hyperoxaluria, urine was also sent for glycolate: creatinine ratio as well as measurement of L-glycerate.…”
Section: Methodsmentioning
confidence: 99%
“…Normal values considered as 100–460 μmol/day/1.73 m 2 of oxalate excretion. (Adequate collection was estimated via measuring 24 h creatinine of 0.1–0.2 mmol/kg/day) [9]. In cases of persistent hyperoxaluria, urine was also sent for glycolate: creatinine ratio as well as measurement of L-glycerate.…”
Section: Methodsmentioning
confidence: 99%
“…This is because they are less susceptible to episodic variations in excretion related to factors such as time of day and food intake (42,50,81) that can potentially skew the interpretation of spot samples. Indeed, comparisons of these two measures have demonstrated that the oxalate-to-creatinine ratio in spot urine samples cannot directly substitute for a 24-h collection as part of a metabolic evaluation (11,43,62).…”
Section: Conflicting Phenotypical Characteristics Of the Sat-1-ko Mouse Modelmentioning
confidence: 99%
“…16 Outcomes in PH3 are thought to be more favourable, 17 and only one case of PH3 has been reported to have ESRF. 18 However, the level of hyperoxaluria in PH3 overlaps with PH1 and PH2, 19 so the natural history may not yet be clearly defined for this relatively newly described disease. Prevalence estimates from public whole exome sequencing in the USA give a figure of $7 per million for PH3, 18 which is much higher than the reported prevalence of PH1 ($1 per million in Europe 20 ) or PH2.…”
Section: Introductionmentioning
confidence: 99%